Konferencja „Problemy syberyjsko-polskiej historii i dialog kultur” - LEOŃCZYK , Sergiusz (Historia i Świat, 2014)
Overview and description of the Scientific Conference "Problems of Siberian-Polish history and dialogue of cultures" in Wrocław (2013.09.5-6).